Clinico-Pathologic Conference: Case 4 - Muramatsu, Takashi (Springer US, 2010)
A 13-month-old Japanese boy presented with painless swelling in a left mandible and cheek. Intraoral examination revealed swelling in the left mandible and hemorrhage of oral mucosa due to biting. CT images revealed a wide osteolytic lesion of the left mandible with floating teeth. Biopsy was carried out and histopathological diagnosis was discussed.